ASPECTS OF THE FORMATION OF TEACHER PROFESSIONAL COMPETENCE (American Journal of Pedagogical and Educational Research, 2023)
The goal of the National Training Program is to radically reform the field of education, to make it a complete halos of ideological views and sarqits from the past, to create a national system of highly qualified training of personnel that meets high spiritual and moral requirements at the level of developed democratic states. The educator is responsible to the Society for educational and educational work in his specialty. He must have the right to a teacher, teacher, teacher, teacher, educator, educator, educator, or, more precisely, the owner of professional competence, in conjunction with the improvement of his professional training on a regular basis.In the article, the aspects of the formation of teacher professional competence are studied pedagogically.